NAP Trainning Guna Optimalisasi Tumbuh Kembang Anak Pada Pra Sekolah di TK Satu Atap Ketompen Pajarakan - Yulia Rachmawati Hasanah; Alwin Widhiyanto (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Sleeping for a child is as important as eating, drinking and playing, because many children neglect their sleep time because they play on their cellphones. This community service aims to increase parents' knowledge and understanding about NAP Training in order to optimize the growth and development of pre-school age children. This activity is carried out using counseling and training methods for mothers who have pre-school age children with the material presented including the concept of sleep, sleep time according to age, benefits of sleep, sleeping techniques and methods for children, the concept of growth and development, children's growth and development according to age stages. . The activities were carried out at the One Roof Kindergarten in Ketompen Village which was attended by 41 mothers. The results obtained were truly extraordinary where almost all participants (97%) were able to answer the questions asked.